Glass Fiber Reinforced Polycarbonate Composites for Laser Direct Structuring and Electroless Copper Plating. Issue 4 (26th February 2020) - Yu, Zhixing; Wang, James H.; Li, Yingcheng; Bai, Yu
Abstract : Glass fiber (GF) reinforced polycarbonate (PC) composites were prepared for laser direct structuring (LDS) applications. A small amount of styrene–maleic anhydride (SMA) was introduced to enhance GF/PC interfacial interactions. The PC/SMA/GF LDS composites using metal complex as LDS additive were investigated for applicability in copper circuit development. Rough surface patterns by laser irradiation under different laser parameters were measured by microscopy and Fourier infrared spectrometry. Copper particles and plating layer by subsequent electroless copper plating procedure was observed using microscopy. Thickness of plating layer and adhesion between layer and matrix were also evaluated. The results showed that laser repetition and scanning speed led to different resolutions and ablated surfaces without structural changes of composites. Copper particles gradually deposited, grew, and interconnected during metallization procedure. Plating layer was successfully formed at an optimum LDS additive loading, and appropriate scanning speed and repetition of laser. In addition, the plating layer displayed disparate thickness and distribution, owing to different activated surfaces by irradiation. Severe ablation or unetched parallel regions resulted in leaky or discontinuous plating layer. Better plating microstructure and higher adhesion were obtained for the composite material with 1.0 wt% LDS additive loading, supporting its extensive development and practical application in LDS technology. POLYM. ENG. SCI., 60:860–871, 2020. © 2020 Society of Plastics Engineers